Effect of carp pituitary extract dose and latency period combinations on the stripping response of Clarias batrachus (Linnaeus, 1758) during induced spawning operation - Sahoo, S. K.; Giri, Shiba Shankar; Paramanik, M. (Indian Journal of Fisheries, 2013)
The stripping response of Clarias batrachus was evaluated at five doses of carp pituitary extract (10, 20, 30, 40 and 50 mg kg -1 body weight of female) administration in combination with five latency periods (11, 14, 17, 20 and 23 h). The females did not respond to stripping when injected 10 and 20 mg pituitary dose and stripped respectively at 11-14 and 11 h latency period. A significant (p